Association Between Employment Status and Short Sleep Duration Among Middle-Aged Japanese: the Survey on Time Use and Leisure Activities. - Maeda, Mitsuya; Filomeno, Ronald; Kawata, Yumi; Sato, Tomoyo; Maruyama, Koutatsu; Wada, Hiroo; Ikeda, Ai; Tanigawa, Takeshi (International Journal of Behavioral Medicine, 2020)
Background: Short sleep duration (SSD) is reported to be highly associated with socio-economic status. There are few studies on the relationship between employment status and SSD in Japan. Method: The authors used the 2006 Survey on Time Use and Leisure Activities conducted by the Ministry of Internal Affairs and Communications Japan, which provides representative samples of Japanese people. The anonymous data of 120,783 people aged 30–59 years were analyzed. Authors defined five categories of employment status: "unemployed," "regularly employed," "non-regularly employed," "self-employed," and "other." Authors also defined a sleep duration shorter than 5 h per night as SSD. Multivariable-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of SSD using regular employment as the reference group were calculated using the logistic regression model, adjusting for potential confounding factors, i.e., age, marital status, education level, communication device use, and the amount of time spent on various daily activities. Results: The prevalence of SSD was 2.8% (1639/58,308) in men and 3.2% (1976/62,475) in women. The multivariable-adjusted OR (95% CI) of SSD for the self-employed was 0.78 (0.65–0.92) in men and 1.78 (1.43–2.21) in women after adjustment for potential confounding factors, i.e., age, marital status, education level, and communication device use. Further adjustment for the time spent on daily activities revealed that the OR (95% CI) of SSD for the self-employed was 0.78 (0.65–0.92) in men and 1.89 (1.52–2.36) in women. Conclusion: Self-employed women had a higher prevalence of SSD. By contrast, self-employed men had a lower prevalence of SSD.